P12.10.A Supratentorial glioblastoma with spinal metastasis: a case report with molecular profiling. (5th September 2022) - Jancalek, R; Hendrych, M; Solar, P; Hermanova, M; Slaby, O
Abstract: Background: Glioblastoma (GBM) is regarded as an aggressive brain tumor that rarely develops extracranial metastases. Despite well-investigated molecular alterations in GBM, there is a limited understanding of these associated with the metastatic potential of GBM. Material and Methods: We present a case report of a 43-year-old woman with frontal GBM IDH-wildtype, who underwent gross-total resection followed by chemoradiation. Five months after surgery, the patient was diagnosed with an intraspinal GBM metastasis. Next-generation sequencing analysis of both primary and metastatic GBM tissues was performed using the Illumina TruSight Tumor 170 assay. Results: The number of single nucleotide variants observed in the metastatic sample was more than 2-times higher. Mutations in TP53, PTEN, and RB1 found in the primary and metastatic tissue samples are indicative of the mesenchymal GBM subtype. Among others, in the metastatic sample, there were detected two inactivating mutations (Arg1026Ile, Trp1831Ter) in the NF1 gene, two novel NOTCH3 variants of unknown significance predicted to be damaging (Pro1505Thr, Cys1099Tyr), one novel ARID1A variant of unknown significance (Arg1046Ser), and one gene fusion of unknown significance EIF2B5-KIF5B. Conclusion: Based on the literature evidence, the inactivation of NF1, NOTCH3, and ARID1A could explain, at least in part, the acquired invasiveness and metastatic potential in this particular GBM case. This work was supported by the grant MUNI/A/1408/2021 of the Masaryk University, Brno, Czech Republic, and INTER-EXCELLENCE Programme / INTER-COST project no. LTC20027 of the Ministry of Health, Czech Republic.